Делаем преобразование левой части уравнения:
(корень ( х+4) -3 ) * (19-х)= -(х-19)*(корень (х+4) -3)Уравнение после преобразования:
-(х-19)*(корень(х+4)-3) = х-5Приводим подобные:
-х* корень (х+4) + 19* корень ( х+4) +3х - 57 = х-5Упрощаем:
-х* корень (х+4) + 19 *корень (х+4) +2х -52=0Решаем уравнение:
-(х-19)* корень (х+4) +2х -52=0
Возможные решения: 5 и 12
ответ х=5 и х =12
Делаем преобразование левой части уравнения:
(корень ( х+4) -3 ) * (19-х)= -(х-19)*(корень (х+4) -3)
Уравнение после преобразования:
-(х-19)*(корень(х+4)-3) = х-5
Приводим подобные:
-х* корень (х+4) + 19* корень ( х+4) +3х - 57 = х-5
Упрощаем:
-х* корень (х+4) + 19 *корень (х+4) +2х -52=0
Решаем уравнение:
-(х-19)* корень (х+4) +2х -52=0
Возможные решения: 5 и 12
ответ х=5 и х =12